The Effectiveness Model of Knowledge Sharing in Business Innovation to Improve the Performance of Micro Small and Medium Enterprises - Bramantiyo Eko Putro; Anita Ilmaniati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
Innovation performance can be an important indicator for organizations because it can enhance competitive advantage. In the organizational context, the results of innovation can be drawn by increasing efficiency, productivity, quality, competitive advantage, and market development. Micro, small, and medium entreprises (MSMEs) generally have to face challenges such as limited financial resources, sub-optimal operations, inefficient supply chains, limitations in technology application, and unpreparedness in facing competition and market changes. To be able to face this challenge, MSMEs need to take an innovative approach in business operationsThis study aims to improve understanding of the effectiveness of knowledge sharing in organizations. An understanding of knowedge sharing activities through the business innovation process is expected to be able to produce a mechanism to improve MSME performance. Research data were obtained by distributing questionnaires directly and online to SMEs Data processing is done by testing the conceptual model using PLS-SEM. The conceptual model was tested with 137 samples obtained directly and online from MSME actors. From the test results, it can be seen the factors that encourage knowledge sharing activities so that they can influence business innovation and encourage the performance of MSMEs namely trust, organizational culture, organizational structure, employee attitudes, and motivational methods.